The DNA dioxygenase ALKBH2 protects Arabidopsis thaliana against methylation damage - Meza, Trine J. (Oxford University Press, 2012)
The Escherichia coli AlkB protein (EcAlkB) is a DNA repair enzyme which reverses methylation damage such as 1-methyladenine (1-meA) and 3-methylcytosine (3-meC). The mammalian AlkB homologues ALKBH2 and ALKBH3 display EcAlkB-like repair activity in vitro, but their substrate specificities are different, and ALKBH2 is the main DNA repair enzyme for 1-meA in vivo. The genome of the model plant Arabidopsis thaliana encodes several AlkB homologues, including the yet uncharacterized protein AT2G22260, which displays sequence similarity to both ALKBH2 and ALKBH3. We have here characterized protein AT2G22260, by us denoted ALKBH2, as both our functional studies and bioinformatics analysis suggest it to be an orthologue of mammalian ALKBH2. The Arabidopsis ALKBH2 protein displayed in vitro repair activities towards methyl and etheno adducts in DNA, and was able to complement corresponding repair deficiencies of the E. coli alkB mutant. Interestingly, alkbh2 knock-out plants were sensitive to the methylating agent methylmethanesulphonate (MMS), and seedlings from these plants developed abnormally when grown in the presence of MMS. The present study establishes ALKBH2 as an important enzyme for protecting Arabidopsis against methylation damage in DNA, and suggests its homologues in other plants to have a similar function.